The Incidence of Pharyngeal Cancer in the Republic of Azerbaijan for 2019–2022 - Anar N. Mamedov (Ķazaķstannyṇ Klinikalyķ Medicinasy)
Introduction: Pharyngeal cancer is a rapidly progressing disease that leads to disability. Epidemiological studies are one of the components of the anti-cancer measures. Knowledge of the territorial prevalence of tumors allows us to solve the issues of their prevention and early detection. The aim of the present study was Epidemiological analysis of the incidence of pharyngeal cancer in the Republic of Azerbaijan. Methodology: The analysis of the epidemiological situation was carried out using incidence rate, attack rate and age-standardized rate per 100.000 population from 2019 to 2022 in the Republic of Azerbaijan Results: The incidence rates of pharyngeal cancer in the Republic of Azerbaijan for the period 2019–2022 were varied in the range 1,0–1,2 (men) and 0,5–0,7 (women) . A similar case was observed in attack rates which were 4,9 -5,7 in males, 3,2- 3,5 in females. The highest values of the standardized rates of the incidence of pharyngeal cancer were observed in the age group of 50–59 years and 60–69 years for both sex. Conclusion: The incidence of pharyngeal cancer remained stable over the study period. The incidence of this form of cancer was relatively higher among men than among women.